2021
DOI: 10.3390/sports9100143
|View full text |Cite
|
Sign up to set email alerts
|

Putative Role of MCT1 rs1049434 Polymorphism in High-Intensity Endurance Performance: Concept and Basis to Understand Possible Individualization Stimulus

Abstract: Monocarboxylate transporters (MCTs) have been proposed as important mediators of the exchange between lactate (La−) producer and La− recipient (consumer) cells. Previous studies have suggested that the MCT1 A1470T genotype could be related to different physical performance phenotypes. This study followed the guidelines for Strengthening the Reporting of Genetic Association Studies (STREGA) and aimed to evaluate the distribution of the MCT1 polymorphism rs1049434 in endurance-trained athletes compared to the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Similar findings have been reported in other studies, where the MCT1 major (T) allele was associated with endurance athlete status and athletic performance (Guilherme et al 2021 ; Saito et al 2021 ). In a study by Piscina-Viúdez et al ( 2021 ), although no statistically significant association was found between athletic performance and the MCT1 gene, the MCT T/T genotype was observed to be higher in triathletes compared to the control group. In another study comparing swimmers and runners, it was reported that the frequency of the T allele was higher in swimmers than in runners (Ben-Zaken et al 2015 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Similar findings have been reported in other studies, where the MCT1 major (T) allele was associated with endurance athlete status and athletic performance (Guilherme et al 2021 ; Saito et al 2021 ). In a study by Piscina-Viúdez et al ( 2021 ), although no statistically significant association was found between athletic performance and the MCT1 gene, the MCT T/T genotype was observed to be higher in triathletes compared to the control group. In another study comparing swimmers and runners, it was reported that the frequency of the T allele was higher in swimmers than in runners (Ben-Zaken et al 2015 ).…”
Section: Discussionmentioning
confidence: 87%
“…From 7 articles that met the inclusion criteria related to MCT1 gene polymorphism, 1392 endurance athletes and 3834 controls have been included in the study (Ben Zaken et al 2015 ; Dzitkowska-Zabielska et al 2022 ; Fedotovskaya et al 2014 ; Guilherme et al 2021 ; Piscina-Viúdez et al 2021 ; Saito et al 2021 ; Sawczuk et al 2015 ). When analyzing the MCT1 (rs1049434) SNP genotypes, the overall analysis showed that endurance athletes [OR: 0.17 [0.02; 0.32]] and Caucasian athletes in the subgroup [OR: 0.42 [0.26; 0.58]] had a higher frequency of the T/T genotype ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that a lower dose of butyrate supplementation at around 3.4 g/d might be optimal. Notably, individual variance may exist in the capability of absorbing SCFAs, as recent studies have identified polymorphisms in several SCFA transporters including MCT1 and MCT2 genes ( 135 , 136 ). As mentioned in Section 2, the fermentation of 1 g fiber may correspond to the production of 10 mM SCFAs.…”
Section: Discussion and Future Directionmentioning
confidence: 99%
“…Interestingly, La − disposal, production, and transportation are not only regulated by extrinsic factors such as exercise dose and energy intake (i.e., distal physiology) but also by intrinsic factors like genetic variations in La − -related genes (MCTs) and the microbiota status [ 52 , 53 ]. In recent years, this direct interaction between La − levels and the microbiota status has been reported in different phenotypes, including the obese population and highly trained athletes [ 54 , 55 , 56 ].…”
Section: Physical Exercise–gut Health Relationshipmentioning
confidence: 99%